PENINGKATAN KAPASITAS KADER POSYANDU MELALUI PELATIHAN MENDETEKSI STUNTING DI DESA RASAU JAYA KECAMATAN RASAU JAYA KABUPATEN KUBU RAYA - Desi, Desi; Sulistyaningsih, Ikawati; Jahri, Muhammad; Nopriantini, Nopriantini; Petrika, Yanuarti; Ginting, Martinus; Rafiony, Ayu; Dahliansyah, Dahliansyah; Ulfa, Mauliana (Poltekkes Kemenkes Bandung, 2024)
The limitations of healthcare personnel in Indonesia result in suboptimal health service coverage. Therefore, a participatory development strategy is an effective approach to address the stunting issue. It's called participatory because not only the government but also the community needs awareness and action to tackle this problem. Empowering health cadres in existing community health posts is one solution. Stunting cases often go unnoticed, requiring community empowerment to recognize and understand its signs. Early awareness enables prompt intervention, preventing severe complications. The goal of this community service is to empower the community through health cadres in addressing and preventing stunting issues in the Rasau Jaya Health Center area. Implementing a more participatory community empowerment model in handling stunting problems is also emphasized in the Rasau Jaya Health Center area. The community service method involves enhancing the capacities of cadres through mentoring activities. This includes training, cadre refreshers, socialization, and practical sessions to improve their knowledge and skills. Additionally, raising awareness and knowledge about stunting, its health impacts, and future consequences is crucial. It aims to broaden understanding of prevention and intervention efforts against stunting. Results from the community service in Rasau Jaya Tiga, Kubu Raya, indicate that empowering health cadres successfully enhances knowledge in stunting intervention. Cadres proficiently perform anthropometry and determine the anemia status of pregnant women, reflecting commitment to stunting prevention aligned with community service goals.